2013
DOI: 10.1016/j.ydbio.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of the inositol polyphosphate-4-phosphatase type II Inpp4b in the generation of ovarian teratomas

Abstract: Teratomas are a unique class of tumors composed of ecto- meso- and endodermal tissues, all foreign to the site of origin. In humans, the most common teratoma is the ovarian teratoma. Not much is known about the molecular and genetic etiologies of these tumors. Female carriers of the Tgkd transgene are highly susceptible to developing teratomas. Ovaries of Tgkd/+ hemizygous female mice exhibit defects in luteinization, with numerous corpora lutea, some of which contain central trapped, fully-grown oocytes. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…It has been widely postulated that enhanced PIP3 signaling is the critical factor impacting cancer development; however evidence is accumulating that PI(3,4)P2 dysregulation may also contribute. Loss of INPP4B is associated with metastatic potential or poor prognosis in multiple cancer types, including breast [22,[39][40][41], prostate [42] and ovarian [22,43] cancers, melanoma [44] and leukemia [45,46]. In fewer cases, there are also evidences of altered INPP4A expression in prostate cancer [47] and leukemia [48].…”
Section: Inpp4b In Cancermentioning
confidence: 99%
“…It has been widely postulated that enhanced PIP3 signaling is the critical factor impacting cancer development; however evidence is accumulating that PI(3,4)P2 dysregulation may also contribute. Loss of INPP4B is associated with metastatic potential or poor prognosis in multiple cancer types, including breast [22,[39][40][41], prostate [42] and ovarian [22,43] cancers, melanoma [44] and leukemia [45,46]. In fewer cases, there are also evidences of altered INPP4A expression in prostate cancer [47] and leukemia [48].…”
Section: Inpp4b In Cancermentioning
confidence: 99%
“…Enhanced PI3K/Akt signaling has been identified in many human cancers including mutation or amplification of the genes encoding catalytic subunits of PI3K p110α and p110δ the gene product of PIK3CA and PI3KCD , respectively) (Angulo et al, 2013; Lucas et al, 2014; Perez-Tenorio et al, 2007; Samuels et al, 2004), loss of function of PTEN (Perez-Tenorio et al, 2007), and/or INPP4B (Balakrishnan and Chaillet, 2013; Bertucci and Mitchell, 2013; Gewinner et al, 2009), or mutation and/or amplification of the proto-oncogenes AKT1 and AKT2 (Ruggeri et al, 1998; Staal, 1987). Therefore, the PI3K/Akt pathway is an important target for drug development for treatment of human malignancies as well as for virus infections.…”
Section: Introductionmentioning
confidence: 99%
“…This class II phosphatase is one of the many players involved in the negative regulation of phosphatidylinositol signaling, a pathway of particular interest for targeted therapies in basal-like and triple-negative breast cancers. [144][145][146][147][148] Located on chromosome 4q31.21, the INPP4B locus is commonly deleted in basal-like breast cancers and cell lines. [92][93][94][149][150][151] Previous studies characterizing INPP4B as a tumor suppressor were primarily focused at the genetic level; however, Gewinner et al 93 recently demonstrated successful immunohistochemical analysis of INPP4B and correlation between loss of INPP4B expression and decreased overall breast cancer survival.…”
Section: Discussionmentioning
confidence: 99%